Mas̱navī āb va sarāb - Jamīl Maẓharī (Ejūkešnal Pablišing Hāʾūs, 2012)
Poems; includes editorial introduction
Poems. - In arab. Schrift, Urdu. - Title on t.p. verso in roman: Masnavi aab-o-srab
Keywords: Masnavis; Urdu; Urdu poetry